Parental investment, school choice, and the persistent benefits of intervention in early childhood - Lei Wang; Yiwei Qian; Nele Warrinnier; Orazio P. Attanasio; Scott Rozelle; Sean Sylvia (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2021)
We present evidence from a randomized experiment testing the impacts of a six-month early childhood home-visiting program on child outcomes at school entry. Two and a half years after completion of the program, we find persistent effects on child working memory - a key skill of executive functioning that plays a central role in children's development of cognitive and socio-emotional skills. We also find that the program had persistent effects on parental time investments and preschool enrolment decisions. Children were enrolled earlier and in higher quality preschools, the latter reflecting a shift in preferences over preschool attributes toward quality. Our findings imply an important role for the availability of high-quality subsequent schooling in sustaining the impacts of early intervention programs.
Keywords: J13; I21; I28; H11; 330; Early Childhood Development; Parenting; China; Poverty